OPTIONS OF JORDAN FOREIGN POLICY IN LIGHT OF "DEAL OF THE CENTURY" REGIONALLY AND INTERNATIONALLY - Tarawneh, Sahar; Mubarak Al-Brezat, Mahmoud (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2025)
This study aimed to highlight the options of Jordan’s foreign policy and its political behavior in light of the Deal of the Century regionally and internationally, in addition to identify it by examine the political conditions that prompted the US administration to propose this project, and by clarify its terms and the Jordanian popular and official position on it, as well as future features of the deal of the century, in particular after the American President lose / Donald Trump, and leave of Benjamin Netanyahu from the Israeli prime minister. The study concluded that the Jordan’s foreign policy has come under pressure from America and Israel, and from some of Arab countries supporting the project, in order to change the Jordan’s position rejecting the deal of the century. And these countries have taken advantage of the economic conditions which Jordan suffers from, however, it remained committed to its decision, armed with various options that it used in dealing with this deal. As the option of reconsidering the Jordan-Israel Peace Treaty, and build Arab -Arab relationships based on cooperation, and trying to overcome disputes and achieve Arab solidarity and effective political coordination in their dealings with Israel, as it is a guarantee of stability and security that serves Jordan’s economic and political interests in light of the continued Israeli pressure on it.